The Responsive Strategy of Courier Services Companies on Handling Customer Complaint in Social Media: The Effect on Brand Trust and Customer Loyalty - Kania, Rafiati; Salsabila, Hanumsari Nurul (Journal of Marketing Innovation (JMI), 2023)
Information technology development allows consumers to express their complaints on platforms such as social media. Twitter trending topic of K-POP merchandise shipping negligence to Indonesian consumers evokes courier service urgency to handle their customer complaints appropriately. This study aims to investigate how potential customers evaluate courier service brand responses to customer complaints on social media that influence consumer trust and loyalty. By integrating the literature on perceived justice in service recovery and brand feedback in social media communication, this study examines the effect of brand feedback, procedural justice, and interactional justice in the company response to customer complaints on potential customer trust in the brand (brand trust) and customer loyalty toward the courier service brand. A total of 333 respondents participated in this survey and confirmed the research model by the PLS-SEM method as data analysis. The main results include the two-way interaction effect of brand feedback and procedural justice on trust and the mediating effect of brand trust on customer loyalty. However, the interactional justice effect becomes insignificant in influencing trust and customer loyalty. This study provides practical implications for courier service companies on how to effectively respond to customer complaints on social media.